DAYA SAING KOPI ARABIKA KALOSI - Rahmawaty A.Nadja; Andi Sitti Halimah; Sabri Sabri; Hasbianah Hasbianah (Agros Journal of Agriculture Science, 2023)
Coffee is one of the leading plantation commodities that has a significant contribution to the Indonesian economy, including sources of income for farmers, producers of industrial raw materials, and job creation. This study aims to analyze the competitiveness of the Arabica Kalosi coffee commodity in Enrekang Regency. The analysis method uses Policy Analysis Matrix (PAM) to determine the Private Cost Ratio (PCR) and Domestic Resource Cost Ratio (DRC) which determine the value of competitive and comparative advantage. The results of this study indicate that the Kalosi Arabica coffee commodity has competitiveness in terms of competitive and comparative advantages as indicated by the PCR value <1 and DRC <1, the PCR and DRC values are 0.37 and 0.30.INTISARIKopi merupakan salah satu komoditas unggulan perkebunan yang memiliki kontribusi cukup besar dalam perekonomian Indonesia, antara lain sumber pendapatan petani, penghasil bahan baku industri, dan pencipta lapangan kerja. Penelitian ini bertujuan untuk menganalisis daya saing komoditi kopi Arabika Kalosi Kabupaten Enrekang. Metode analisis menggunakan Policy Analysis Matrix (PAM) untuk mengetahui Rasio Biaya Privat (PCR) dan Rasio Biaya Sumberdaya Domestik (DRC) yang menentukan nilai keunggulan kompetitif dan komparatif. Hasil penelitian ini menunjukkan bahwa komoditas kopi Arabika Kalosi memiliki daya saing dilihat dari keunggulan kompetitif dan komparatif  yang ditunjukkan dengan nilai PCR <1 dan DRC <1, nilai PCR dan DRC yakni 0,37 dan 0,30.